CATALYSTS OF WORD-OF-MOUTH BEHAVIOR: EXPLORING THE IMPACT OF SERVICE QUALITY, BRAND IMAGE, AND STUDENT COMMITMENT AT UNIVERSITAS PUTRA INDONESIA 'YPTK' PADANG - Wahyu Juari Setiawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to assess the concurrent and partial effects of Service Quality, Brand Image, and Student Commitment on Word of Mouth (WOM) behavior within the context of Universitas Putra Indonesia “YPTK” Padang. Data was collected through a survey employing questionnaires distributed to a sample of 100 respondents. Utilizing multiple regression analysis and correlation techniques, the research findings indicate that Service Quality, Brand Image, and Student Commitment collectively contribute to the prediction of Word of Mouth behavior. Individually, each factor also demonstrates significant influence on WOM behavior, as demonstrated by the computed t-values exceeding the critical t-values at a significance level (α) of less than 0.05. The outcomes of the simultaneous hypothesis test (F-test) further underscore that the combined influence of Service Quality, Brand Image, and Student Commitment significantly affects WOM behavior. This is evident from the calculated F-value surpassing the critical F-value, with a significance level of less than 0.05. In conclusion, the research substantiates the substantive influence of Service Quality, Brand Image, and Student Commitment on Word of Mouth behavior within the milieu of Universitas Putra Indonesia “YPTK” Padang. Furthermore, these factors collectively account for a considerable proportion of the observed WOM behavior, as illuminated by the coefficient of determination